Assessment of Corticoadrenal Reserve Through Salivary Steroids - Cardoso, Estela M. del Luján (2002)
Recent reports have reinforced the usefulness of salivary cortisol (SAF) in the evaluation of cortisol dynamics and the diagnosis of Cushing syndrome. However few data are available on the usefulness of SAF and salivary aldosterone (SAL) in response to corticotrophin (ACTH) stimulus. The aim of the authors ‘ study was to standardize the response of SAF and SAL to the intramuscular injection of 250 mg of synthetic human ACTH in 21 healthy patients. Salivary samples were obtained in baseline conditions and during 30,60,90,120 minutes after ACTH administration. The results showed that all healthy  volunteers achieved SAF and SAL concentrations of at least 40.0 nmol/L and 100.0 pmol/L , respectively , after the stimulus. The clinical usefulness of this test was confirmed when patients with known adrenal dysfunction were studied. In three patients with primary adrenal insufficiency, blunted SAF and SAL responses were obtained. Six patients with secondary adrenal insufficiency demonstrated subnormal or blunted SAF and normal SAL responses after ACTH stimulation. Corticoadrenal reserve can be easily , noninvasively, and accurately investigated through the simultaneous measurement of salivary cortisol and aldosterone in response to corticotrophin. Salivary aldosterone was helpful in the differential diagnosis of adrenocortical hypofunction.